2011
DOI: 10.1007/s11249-011-9825-3
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior of Nanostructured Al and Al–B4C Nanocomposites Produced by Mechanical Milling and Hot Extrusion

Abstract: Wear properties of a nanostructured matrix of Al prepared via mechanical milling and hot extrusion were investigated before and after incorporation of B 4 C nanoparticles. The sample powders were milled for a period of 20 h to produce nanopowders. Mechanical milling was used to prepare nanocomposite samples by addition of 2 and 4 wt% of B 4 C nanoparticles into the Al matrix. A pinon-disk setup was used to evaluate the wear properties of the hot extruded samples under dry condition. The results revealed a lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 39 publications
3
8
0
1
Order By: Relevance
“…In fact, despite reduction of density with the increase of SiC content, the nano reinforcement could enhance the hardness due to its hardening effects and its intrinsic hardness. Alizadeh and Taheri-Nassaj [10], Dong et al [23], and Canakci [6] also reported similar observations in their investigation. The improvement of hardness is related to the material strength enhancement.…”
Section: Composite Interfaces 583supporting
confidence: 73%
See 1 more Smart Citation
“…In fact, despite reduction of density with the increase of SiC content, the nano reinforcement could enhance the hardness due to its hardening effects and its intrinsic hardness. Alizadeh and Taheri-Nassaj [10], Dong et al [23], and Canakci [6] also reported similar observations in their investigation. The improvement of hardness is related to the material strength enhancement.…”
Section: Composite Interfaces 583supporting
confidence: 73%
“…In all of these techniques, the load can be applied either quasi-statically or dynamically. Hot pressing, [8] hot isostatic pressing [9] and hot extrusion [10] are typical examples of quasi-static loading. As stated above, the composites can also be produced under dynamic compaction [11,12] or shock wave consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Cold welding, or the separation of particles caused by adhering to the surface, is the dominant mechanism in adhesive wear. In this mechanism, separation of the particles from the surface is associated with plastic deformation [28][29][30]. One very important point about adhesion mechanism that must be noted is the formation of tribological layer in this type of wear.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Boron carbide (B 4 C), one of the most important engineering ceramics, has been extensively used in various industrial fields of cutting tools [1], nozzles [2], astronomical applications [3], ballistic armour [4], thermal neutron detectors [5] and as an enhancing phase in alloys [6][7][8], because its special atomic structure and composition lends itself to outstanding physical and mechanical properties [9][10][11][12][13], such as a high melting point (2450 ℃), high hardness (30 ~ 45 GPa), excellent chemical inertness, low density (2.52 g•cm -3 ) and strong absorption neutron ability. Nevertheless, the high friction coefficient of B 4 C (0.4 ~ 0.9) seriously impedes its further application.…”
Section: Introductionmentioning
confidence: 99%